Caregiver–Oncologist Prognostic Concordance, Caregiver Mastery, and Caregiver Psychological Health and Quality of Life. (13th February 2021) - Loh, Kah Poh; Mohamed, Mostafa R.; Kadambi, Sindhuja; Culakova, Eva; Xu, Huiwen; Magnuson, Allison; Flannery, Marie; Duberstein, Paul R.; Epstein, Ronald M.; McHugh, Colin; Nipp, Ryan D.; Trevino, Kelly M.; et al.
Abstract: Background: Caregivers of adults with cancer often report a different understanding of the patient's prognosis than the oncologist. We examine the associations of caregiver–oncologist prognostic concordance with caregiver depressive symptoms, distress, and quality of life (QoL). We also explore whether these relationships differed by caregiver environment mastery, an individual's sense of control, and effectiveness in managing life situations. Materials and Methods: We used data from a national geriatric assessment cluster‐randomized trial (URCC 13070) that recruited patients aged 70 years and older with incurable cancer considering any line of cancer treatment at community oncology practices, their caregivers, and their oncologists. At enrollment, caregivers and oncologists estimated the patient's prognosis (0–6 months, 7–12 months, 1–2 years, 2–5 years, and >5 years; identical responses were concordant). Caregivers completed the Ryff's environmental mastery at enrollment. At 4–6 weeks, caregivers completed the Patient Health Questionnaire‐2 (depressive symptoms), distress thermometer, and 12‐Item Short‐Form Health Survey (quality of life [QoL]). We used generalized estimating equations in models adjusted for covariates. We then assessed the moderation effect of caregiver mastery. Results: Of 411 caregiver–oncologist dyads (mean age = 66.5 years), 369 provided responses and 28% were concordant. Prognostic concordance was associated with greater caregiver depressive symptoms (β = 0.30; p = .04) but not distress or QoL. A significant moderation effect for caregiver depressive symptoms was found between concordance and mastery ( p = .01). Specifically, among caregivers with low mastery (below median), concordance was associated with greater depressive symptoms (β = 0.68; p = .003). Conclusions: Caregiver–oncologist prognostic concordance was associated with caregiver depressive symptoms. We found a novel moderating effect of caregiver mastery on the relationship between concordance and caregiver depressive symptoms. Implications for Practice: Caregiver–oncologist prognostic concordance is associated with greater caregiver depressive symptoms, particularly in those with low caregiver mastery. When discussing prognosis with caregivers, physicians should be aware that prognostic understanding may affect caregiver psychological health and should assess their depressive symptoms. In addition, while promoting accurate prognostic understanding, physicians should also identify strengths and build resilience among caregivers. Abstract : Patients and caregivers need an accurate understanding of prognosis to help them make informed treatment decisions and to prepare for the future. This article examines the association of caregiver–oncologist concordance in their estimates of patient length of life with caregiver depressive symptoms, distress, and quality of life.